Sustainability Communication Interdisciplinary Perspectives and Theoretical Foundation - Godemann, Jasmin; Michelsen, Gerd.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Modern and professional communication is required to realise the goal of sustainability in society. This book develops a theoretical and empirical framework, integrating interdisciplinary perspectives from communications theory, psychology, sociology, educational sciences, systems theory and constructivism. Its aim is to inform the establishment of sustainability communication. Complementing this theoretical framework, the book provides methods and concepts in a range of fields such as corporate practice, education and media. The book addresses the scientific community and students as well as communicators in all categories of sustainability communication.
I. Mapping Sustainability Communication -- 1. Sustainability Communication - An Introduction -- 2. Strong Sustainability as a Frame for Sustainability Communication -- 3. Sustainability Communication an Integrative Approach -- 4. Sustainable Communication as An Inter- and Transdisciplinary Discipline -- II. Framework of Sustainability Communication -- 5. Sociological Perspectives on Sustainability Communication -- 6. Psychological Aspects of Sustainability Communication -- 7. Media Theory and Sustainability Communication -- 8. Communication Theory and Sustainability Discourse -- 9. Communicating Education for Sustainable Development -- 10. Sustainability Communication: A Systemic-constructivist Perspective -- III. Practice of Sustainability Communication -- 11. Climate Change as an Element of Sustainability Communication -- 12. Biodiversity and Sustainability Communication -- 13. Communicating Sustainable Consumption -- 14. Corporate Sustainability Reporting -- 15. Computer Support for Cooperate Sustainability Communication -- 16. Participation: Empowerment for Sustainable Development -- Index.
Keywords: Environmental sciences; Science (General).; Sustainable development; Humanities; Social sciences; Environment; Sustainable Development; Environment, general; Social Sciences, general; Interdisciplinary Studies; Science, general